2008
DOI: 10.1007/s00216-008-2346-8
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid method for the determination of ethylenebisdithiocarbamate fungicides in fruits and vegetables using liquid chromatography with tandem mass spectrometry

Abstract: A simple and rapid method for determining ethylenebisdithiocarbamates (EBDCs; mancozeb, maneb, and zineb) in fruits and vegetables is described. EBDCs are transformed into dimethylethylenebisdithiocarbamate (EBDC-dimethyl) by methylation after their decomposition with ethylenediaminetetraacetic acid (EDTA). These processes were performed simultaneously in this method. Dimethyl sulfate was used as the methylation reagent, and acetonitrile extracts obtained from partitioning with anhydrous magnesium sulfate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 18 publications
0
13
0
9
Order By: Relevance
“…The sample treatment step is somehow a bottleneck for the development of large scale screening procedures in pesticide residues analysis. Troublesome compounds (i.e., chlormequat, paraquat, dithiocarbamates, glyphosate) not recovered with the generic sample treatment procedures should be analyzed with single-residue methods (Andersen, Bille, & Granby, 2007;Crognorac, Schmauder, & Schwack, 2008;Hanke, Singer, & Hollender, 2008;Hayama & Takada, 2008;Esparza, Moyano, & Galceran, 2009). Based on the cited literature, simpler sample treatment procedures are usually required for LC-MS analysis (Table 1) while more exhaustive sample pre-treatment procedures involving additional clean-up steps have been applied in GC-MS analysis (Table 2).…”
Section: Martosmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample treatment step is somehow a bottleneck for the development of large scale screening procedures in pesticide residues analysis. Troublesome compounds (i.e., chlormequat, paraquat, dithiocarbamates, glyphosate) not recovered with the generic sample treatment procedures should be analyzed with single-residue methods (Andersen, Bille, & Granby, 2007;Crognorac, Schmauder, & Schwack, 2008;Hanke, Singer, & Hollender, 2008;Hayama & Takada, 2008;Esparza, Moyano, & Galceran, 2009). Based on the cited literature, simpler sample treatment procedures are usually required for LC-MS analysis (Table 1) while more exhaustive sample pre-treatment procedures involving additional clean-up steps have been applied in GC-MS analysis (Table 2).…”
Section: Martosmentioning
confidence: 99%
“…Approximately 60% of the methodologies reviewed in the present article covering the last 3 years are based on LC-QqQ-MS. Even though the majority of methodologies proposed in the field of pesticide residue-analysis focus on the development of multi-residue multi-class methods using LC-QqQ-MS, several deal with single-residue and/or single-class applications especially in cases where the definition of the residue in the MRL (Commission Regulations (EC), 396/2005, 149/2008, 839/2008 encompass metabolites and transformation products of the parent compound (Goto et al, 2006b;Soler et al, 2006a;Barceló & Petrovic, 2007;Hengel & Miller, 2007;Perreau et al, 2007;Poulsen et al, 2007;Sannino, 2007;Caboni et al, 2008;Crnogorac, Schmauder, & Schwack, 2008;Hayama & Takada, 2008;Hanke, Singer, & Hollender, 2008;Koesukwiwat, Sanguankaew, & Leepipatpiboon, 2008;Sarais et al, 2008;Xinyi et al, 2008;Esparza, Moyano, & Galceran, 2009;Tokman et al, 2009). Nowadays, parent compounds and their transformation products can be analyzed with LC-QqQ-MS in the same chromatographic run; this is especially helpful for official and/or routine laboratories.…”
Section: Ms Analysis Of Pesticidesmentioning
confidence: 99%
“…In this case, the addition of a conventional EDTA solution [12][13][14][15][16][17][21][22][23][24][25] was not appropriate, as the LC-MS/MS peak corresponding to EDTA overlapped with the peak originating from PBMe. We therefore investigated the effect of the NaHCO 3 concentration on the sample prior to methylation, using propineb, mancozeb, and thiuram as representative compounds for PB, EB, and DD, respectively, as previously mentioned.…”
Section: Optimization Of the Sample-preparation Methodsmentioning
confidence: 99%
“…Thus, we attempted to prevent degradation by adding DTT as a stabilizer, as it has been reported that reducing agents are effective stabilizers. 26) In this case, we could not select cysteine, [12][13][14][15][16][17][22][23][24][25] as the retention times for the methylated form of cysteine and DDMe were comparable under the same MS/MS conditions due to their similar molecular weights. Thus, we also investigated the effect of the DTT concentration on the samples and found that degradation was prevented in a number of cases, resulting in enhanced methylation rates.…”
Section: Optimization Of the Sample-preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation